Analysis of Crude Oil Price and Household Income in the State of Louisiana (International Research in Economics and Finance, 2021)
A large part of determining gas price rests on the price paid for crude oil. There are several variables that can affect gas prices such as global and domestic demand and production supply, unpredictability in the Middle East, fluctuating weak United States dollar value, natural disasters, and household income. Some explanations are provided about some of the previously mentioned variables, but the focus of analysis is Louisiana crude oil price as it relates to household income. The method that was used in this current research is the regression model and the estimated linear regression equation least square method. A scatter plot is provided to display the relationship between variables. A chart that shows historical data of crude oil prices and a correlation of events as they relate to the rise or fall of oil price level is also provided. The multivariate correlation matrix shows that some variables are significant at p- value of 0.05. The largest values indicated that the crude oil price per barrel was strongly positive (r = 0.9530) linked with Louisiana gas price while Louisiana median household income (r = 0.0898), unemployment rate in Louisiana (r = 0.3398). This paper evaluates crude oil price as a dependent variable and how it relates to major independent variables using a general linear regression. The result shows that a high unemployment rate in Louisiana lowers the Louisiana gas price and therefore inhibits oil and gas market. it is highly recommended that the U.S. could continue to increase drilling activities in the state of Louisiana all it wants but it is hard to expect greater domestic production to move gas prices by more than two percentage points in the next few years. i